Alternative and complementary medicine in neurological disorders and neurological disability patients: Prevalence, factors, opinions and reasons - Paul Carrillo-Mora; Marlene A. Rodríguez-Barragán; Jimena Quinzaños-Fresnedo; María del Refugio Pacheco-Gallegos; María Soto-Lara; Monserrat Velázquez-Ortega; María Fernanda Villarreal-Azamar; Ilse Jocelyn Aguirre-Medina; Mariana Rubalcava-Gracia-Medrano (Complementary Therapies in Medicine, 2023)
Objectives: This cross-sectional study is aimed to investigate the prevalence of the use of complementary and alternative medicine (CAM), types of CAMs used, as well as reasons and factors found in patients with neurological diseases or neurological disability. Methods: An anonymous, self-administered survey was designed to collect information about demographics, personal medical history, CAM usage habits, and different opinions about CAM vs. conventional medicine (CM). The survey was applied by non-medical personnel in a rehabilitation hospital to patients older than 18 years, with a confirmed diagnosis of neurological disorder or neurological disability. Results: 453 patients were included, 59.7 % were female. Mean age: 49 years (SD: 18.2). 200 patients (44.2 %) had a history of chronic diseases. Depression was found in 139 patients (30.7 %). Neurological disorders were: peripheral neuropathy: 97 (21.4 %), headache or migraine: 78 (17.2 %), neurodegenerative diseases: 69 (15.2 %) and stroke: 58 (12.8 %). 60.2 % (n = 273) had some degree of disability. Prevalence of CAM use was 36 % (n = 163). Most common CAMs were: Biological therapies: 133 (71.1 %), energy-based therapies: 63 (33.7 %) and body manipulation therapies: 51 (27.3 %). Reasons to use CAM were: “to complement the pharmacological treatment” (45 = 27.6 %), and “treatment failure with CM” (43 = 26.4 %). Finally, older age (p = 0.0280) and having a chronic disease (p = 0.0229) or depression (p < 0.001) were the factors associated with the current use of CAM. Conclusion: One third of patients with neurological pathologies use CAM, the most popular type of CAM is biologic therapies. As in other pathologies, CAM use was associated with older age, history of depression, and chronic diseases. Therefore, it is suggested that physicians routinely ask patients about the use of CAM, if they need more information about CAM, and even verify the possibility of drug interactions or adverse effects.